Perbedaan indeks berat badan menurut tinggi badan sebelum dan sesudah pemberian makanan tambahan balita underweight - Anggraeni, Mulia; Rakhma, Luluk Ria; Kisnawaty, Sudrajah Warajati (Holistik Jurnal Kesehatan, 2025)
Background: Nutritional problems in toddlers, particularly underweight, remain a public health challenge in Indonesia. This condition can be influenced by consumption patterns, infections, and indirect factors, such as food access, parenting, sanitation, and health services. Furthermore, mothers' low nutritional knowledge also contributes to children's nutritional status. Lack of supplementary feeding programs is a major factor in the high rates of stunting and wasting in Indonesia. Continuous improvement in the distribution, education, and supervision of supplementary feeding programs is crucial to producing a healthier and more productive generation. Purpose: To determine the difference in body mass index according to height before and after the supplementary feeding programs to underweight infants. Method: A quantitative study using a quasi-experimental method was conducted at the Mojolaban Community Health Center, Sukoharjo, in April 2025. The independent variable was supplementary feeding program, while the dependent variable was weight-for-height. The sampling technique used total sampling, resulting in a sample size of 104 participants based on inclusion and exclusion criteria. Data analysis was performed using univariate analysis in the form of frequency distribution and bivariate analysis using the Wilcoxon test. Results: The mean ± SD of BB/TB Before was −1.7±0.7, with a range of values between −4.90 and −0.30. The mean BB/TB after intervention was −1.69 ± 0.7, with a range of values between −4.76 and 0.28. The Wilcoxon test results showed a p-value of 0.015, indicating a statistically significant difference between BB/TB before and after the supplementary feeding program implementation. Conclusion: Supplementary feeding program for 30 days has been shown to have a significant effect on improving the nutritional status of underweight infants. There was an increase in the Z-score for weight-for-height and the proportion of infants with normal nutritional status, indicating that supplementary feeding program intervention is effective in improving the nutritional status of infants.   Keywords: Body Weight Index; Height; Supplementary Feeding; Toddler; Underweight.   Pendahuluan: Masalah gizi pada balita, khususnya underweight, masih menjadi tantangan kesehatan masyarakat di Indonesia. Kondisi ini dapat dipengaruhi oleh pola konsumsi, infeksi, dan faktor tidak langsung, seperti akses pangan, pola asuh, sanitasi, serta layanan kesehatan. Selain itu, rendahnya pengetahuan ibu tentang gizi juga berkontribusi terhadap status gizi anak. Kurangnya pemberian makanan tambahan (PMT) menjadi faktor utama tingginya angka stunting dan wasting di Indonesia. Perbaikan distribusi, edukasi, dan pengawasan program PMT secara berkelanjutan sangat diperlukan untuk menghasilkan generasi yang lebih sehat dan produktif. Tujuan: Untuk mengetahui perbedaan indeks berat badan menurut tinggi badan (BB/TB) sebelum dan sesudah pemberian makanan tambahan (PMT) pada balita underweight. Metode: Penelitian kuantitatif dengan metode quasi eksperimental, dilaksanakan di Puskesmas Mojolaban, Sukoharjo pada bulan April 2025. Variabel independen dalam penelitian ini adalah Pemberian Makanan Tambahan (PMT), sedangkan variabel dependen adalah berat badan menurut tinggi badan. Teknik pengambilan sampel menggunakan total sampling, didapatkan jumlah sampel sebanyak 104 partisipan. Analisis data yang digunakan adalah univariat dalam bentuk distribusi frekuensi dan bivariat menggunakan uji Wilcoxon. Hasil: Nilai rata-rata (Mean±SD) BB/TB sebelum adalah −1.7±0.7, dengan rentang nilai antara −4.90 hingga −0.30. Nilai rata-rata BB/TB sesudah adalah −1.69±0.7, dengan rentang nilai antara −4.76 hingga 0.28. Hasil uji Wilcoxon menunjukkan p-value sebesar 0.015, yang mengindikasikan adanya perbedaan yang signifikan secara statistik antara BB/TB sebelum dan sesudah pemberian PMT. Simpulan: PMT selama 30 hari terbukti berpengaruh signifikan terhadap perbaikan status gizi balita underweight. Terdapat peningkatan nilai Z-score BB/TB dan proporsi balita dengan status gizi normal, yang menunjukkan bahwa intervensi PMT efektif dalam meningkatkan status gizi balita.   Kata Kunci: Balita; Indeks Berat Badan; Makanan Tambahan; Tinggi Badan; Underweight.